2005
DOI: 10.1299/jsmeb.48.562
|View full text |Cite
|
Sign up to set email alerts
|

Computational Validation for Flow around a Marine Propeller Using Unstructured Mesh Based Navier-Stokes Solver

Abstract: Results of computational fluid dynamics validation for flow around a marine propeller are presented. Computations were performed for various advance ratios following experimental conditions. The objectives of the study are to propose and verify a hybrid mesh generation strategy and to validate computational results against experimental data with advanced computational fluid dynamics tools. Computational results for both global and local flow quantities are discussed and compared with experimental data. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 15 publications
3
18
0
1
Order By: Relevance
“…That is, how far the domain extends upstream, downstream, and radially. Previously, Rhee and Joshi [4] demonstrated that an extended domain 2*£> downstream gave the same results as a domain that extended only 0.72*D downstream. As previously stated, the domain used for this study did extend 2*D downstream, so dependency on domain extent was not studied.…”
Section: Full 5-bladed Propeller Meshmentioning
confidence: 84%
“…That is, how far the domain extends upstream, downstream, and radially. Previously, Rhee and Joshi [4] demonstrated that an extended domain 2*£> downstream gave the same results as a domain that extended only 0.72*D downstream. As previously stated, the domain used for this study did extend 2*D downstream, so dependency on domain extent was not studied.…”
Section: Full 5-bladed Propeller Meshmentioning
confidence: 84%
“…Fluent is a unstructured mesh based finite volume CFD code implementing cavitation models, low Reynolds number two-equation type turbulence models, sliding mesh capability, and so on. This code has been already applied to a steady viscous flow around propeller and steady cavitating viscous flow around propeller 1,2,3,4) . In this study, we chose SIMPLE and PISO algorithms for steady and unsteady problems respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The diameter of the stationary cylindrical domain is 3D and that of the rotating domain is 1.2D. The blades were simply mounted on an infinitely long cylinder, which serves as the hub [6]. Fig.…”
Section: Grid Generation and Numerical Setupsmentioning
confidence: 99%